Note on a meeting of the Eastbourne Trades Council... [to] discuss a national medical service - British Medical Association; Smyth, J. L.
1943-10-223 1943 1940s 7 pages I also asked, having in mind the doctors' advocacy of a full service for everybody, what private patients would expect to get for the extra money which they paid. The doctors said that even though there was a fully efficient service open to everybody, if certain people had money and wished to pay for their own treatment they should be allowed to do so even though they could have got the same treatment through the State scheme. I suggested that where such a person was paying fees to a doctor who was also working the State service, that they were bound to expect preference of some kind and in any case there was bound to be suspicion that they were getting preference. The position would in fact be the same as it is at present, where it is freely alleged that panel patients get very different treatment from private patients. Dr. Young asserted that State Medical Service had not succeeded anywhere and in reply to my query as to whether he had seen the report of certain distinguished surgeons who had just returned from Russia he said that they had been concerned with the specialist services and the organisation of hospitals but had not gone into the question of general practice. He said that some time ago a party of General Practitioners did visit Russia and the report they made was that the services there was anything but satisfactory. He also said that in New Zealand the State Service was a flop. The impression I got from the meeting was that those who were present were not influenced in favour of the B.M.A. Scheme. On the other hand the doctors asked that a reply should be given to each of the points set out on the questionnaire and returned to Dr. Young in an addressed envelope which each delegate had been supplied with by the doctors. I suggested to the Secretary of the Trades Council that in answering the questions the delegates should make it clear that they are in favour of a State Medical Service as most of the questions could not be answered without considerable qualification. I understand that the questionnaire had been drawn up by the medical men in Eastbourne and that it represented their idea of the best way to get public opinion for or against the B.M.A ideas. Apparently the profession throughout the country have been asked by the B.M.A. to sound public opinion presumably in order that they might use the information thus obtained in their negotiations with the Ministry of Health on the Government's White Paper. I understand that the Eastbourne doctors had met a number of other bodies in the town as well as the Trades Council. J.L. Smyth 22nd October, 1945. JLS/EM/156/27.10. 292/847/2/107